3D roughness standard for performance verification of topography instruments for additively-manufactured surface inspection. (1st August 2022) - Jones, Christopher W; Sun, Wenjuan; Boulter, Hal; Brown, Stephen
Abstract: The unique complex topography of additively-manufactured surfaces—and the recent rapid evolution of instruments and techniques to measure them—limits trust in inspection data, in direct conflict with the requirements of application areas such as aerospace, where failure of a part can have serious safety consequences. Topography instrument manufacturers and end-users require measurement standards with a controlled reproduction of representative additively-manufactured surfaces to calibrate, performance-verify and intercompare instruments for inspection tasks, thereby improving confidence in measurement. The design of such a surface texture measurement standard is reported, optimised for optical areal topography-measuring instruments and compatible with x-ray computed tomography instruments. Machined from an additively-manufactured blank, the standard's four sides represent increasing levels of post-processing from the as-deposited surface. Datum features on the measurement standard facilitate direct comparison between topography instruments. Integrated step features support the calibration of an instrument's Z scale. Calibration of a prototype of the standard is reported; the prototype is matched to a typical aerospace Scalmalloy™ additive manufacturing process. The calibration is also a trial application of a large-area chromatic confocal microscope; this instrument appears capable of calibrating relatively rough measurement standards if required to do so. Reference Ra and S -parameter measurements and associated measurement uncertainties are presented, correlation between parameters noted, and choice and consequences of filter settings discussed.